A rare case of oesophageal and gastric fundus necrosis following traumatic splenectomy. Issue 9 (28th September 2022) - Bennett, Laura; Gallagher, James
Abstract: Oesophageal and gastric fundus necrosis are rare clinical entities and have not previously been reported concurrently. This case study describes oesophageal and gastric fundus necrosis in a 71-year-old female who developed chest pain post-splenectomy for infected splenic haematoma in the context of a fall. Upper gastrointestinal endoscopy demonstrated oesophageal and gastric fundus necrosis. This was likely due to multiple factors including comorbidities, hypoperfusion, post-splenectomy state and herpes simplex virus oesophagitis. This finding is an important differential in the unwell patient with chest pain post-splenectomy and investigation with upper gastrointestinal endoscopy could be considered in the absence of another cause.